Critical Legal Theory in Central and Eastern Europe: In Search of Method - Mańko, Rafał (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
Critical legal theory emerged in the United States in the 1970s, at a time when Central and Eastern Europe belonged to the Soviet bloc and was subject to the system of actually existing socialism. Therefore, the arrival of critical jurisprudence into the region was delayed. In Poland, the first texts on critical and postmodern legal theory began to appear at the end of the 1990s and the beginning of the 2000s. Lech Morawski’s monograph, characteristically entitled What Legal Scholarship Has to Gain from Postmodernism?, published in 2001, officially inaugurated a broader interest in postmodern legal theory. Adam Sulikowski has been the main representative of critical legal theory in Poland, developing a postmodern theory of constitutionalism. Other sub-fields of postmodern and critical legal theory, gradually developing in Central European jurisprudence, include such areas as law and literature, law and ideology, law and neocolonial theory, as well as feminist jurisprudence. There is a noticeably growing influence of critical sociology and critical discourse analysis which seem to be a promising paradigm for invigorating critical legal theory from an empirical perspective. The concept of “the political”, in the sense used by Chantal Mouffe, has been evoked to propose a “political theory of law” conceived as an analysis of the juridical phenomenon through the lens of the political. Recently, it has found its concrete applications in the political theory of judicial decision-making.